Rotigotine effects on early morning motor function and sleep in Parkinson's disease: A double-blind, randomized, placebo-controlled study (RECOVER) - Trenkwalder, Claudia; Kies, Bryan; Rudzinska, Monika; Fine, Jennifer; Nikl, Janos; Honczarenko, Krystyna; Dioszeghy, Peter; Hill, Dennis; Anderson, Tim; Myllyla, Vilho; Kassubek, Jan; Steiger, Malcolm; et al. (Movement disorders, 2011)
In a multinational, double‐blind, placebo‐controlled trial (NCT00474058), 287 subjects with Parkinson's disease (PD) and unsatisfactory early‐morning motor symptom control were randomized 2:1 to receive rotigotine (2–16 mg/24 hr [n = 190]) or placebo (n = 97). Treatment was titrated to optimal dose over 1–8 weeks with subsequent dose maintenance for 4 weeks. Early‐morning motor function and nocturnal sleep disturbance were assessed as coprimary efficacy endpoints using the Unified Parkinson's Disease Rating Scale (UPDRS) Part III (Motor Examination) measured in the early morning prior to any medication intake and the modified Parkinson's Disease Sleep Scale (PDSS‐2) (mean change from baseline to end of maintenance [EOM], last observation carried forward). At EOM, mean UPDRS Part III score had decreased by −7.0 points with rotigotine (from a baseline of 29.6 [standard deviation (SD) 12.3] and by −3.9 points with placebo (baseline 32.0 [13.3]). Mean PDSS‐2 total score had decreased by −5.9 points with rotigotine (from a baseline of 19.3 [SD 9.3]) and by −1.9 points with placebo (baseline 20.5 [10.4]). This represented a significantly greater improvement with rotigotine compared with placebo on both the UPDRS Part III (treatment difference: −3.55 [95% confidence interval (CI) −5.37, −1.73]; P = 0.0002) and PDSS‐2 (treatment difference: −4.26 [95% CI −6.08, −2.45]; P < 0.0001). The most frequently reported adverse events were nausea (placebo, 9%; rotigotine, 21%), application site reactions (placebo, 4%; rotigotine, 15%), and dizziness (placebo, 6%; rotigotine 10%). Twenty‐four‐hour transdermal delivery of rotigotine to PD patients with early‐morning motor dysfunction resulted in significant benefits in control of both motor function and nocturnal sleep disturbances. © 2010 Movement Disorder Society